MORPHOLOGICAL AND VASCULAR CHARACTERISTICS OF THE SUPERFICIAL MUSCLO-APONEUROTIC SYSTEM OF THE ORAL REGION - Ramona Paula Cucu; Marius Valeriu Hînganu; Monica Mihaela Scutariu; Victor-Vlad Costan; Ludmila Lozneanu; Otilia Boișteanu; Delia Hînganu (Romanian Society of Oral Rehabilitation, 2024)
Since the superficial musculo-aponeurotic system of the face (SMAS) of the face is still controversial, we intend to highlight the anatomical and especially vascular differences that exist between different regions of the face. Material and Methods We performed dissection and we examined intraoperatively the oral region, achieving particular aspects. We used HE stain technique as well as IHC particular markers for detecting endhotelial cells, collagen type III fibers and muscle fibers. Results The dissection showed that SMAS presents different areas regarding the mobility. The central portion of each hemifacies presents the greatest degree of mobility and peripheral portions are fixed, as a result of the existence of mounting configurations, skin muscle insertions, but also the different thickness of infraSMAS layer. Discussions The existence of a well established subcutaneous fat layer leaves the facial expressions muscles of without antigravitational support. The density, distribution and topograhpy of the blood vessels differes from a region to another. Conclussions Our results lead to specific improvements of the SMAS surgery and the issues that allow different surgical techniques of mobilization and repositioning of folds in perioral surgery, for reconstruction or face lifting.